The Effect of Product Quality And Product Impact on Customer Satisfaction Purchase Decisions as Intervening Variables - Putri Andriyani S; Agus Arwani (Velocity: Journal of Sharia Finance and Banking, 2021)
The purpose of this study is to determine the effect of product quality and product benefits on customer satisfaction through purchase. The research method uses a quantitative approach. The consumers of Hexsoul were drinking water more than five times in the distributor of Pekalongan City branch Hexsoul drinking water as many as 234 consumers with a sample of 100 respondents using Donald R. Cooper and C. William Emory formulas. The sampling technique uses accidental sampling and then purposive sampling. The data analysis is used in this study is path analysis. The product quality has a positive and significant effect on purchasing decisions with a significance value of 0,000 and a regression coefficient of 0,244, a significance value of 0,000 <0,05 (2) product benefit has a the significance value of 0,000 <0,05 (3) product quality has a positive and significant effect on consumer satisfaction with a significance of 0,002 and regression coefficient value of 0.140, (4) the benefit has a positive and significant effect on consumers satisfaction with a significance of 0.022 and a regression coefficient of 0.140, (5) purchasing decisions have a positive and significant effect on consumer satisfaction with a significance of 0,000 and a regression coefficient of 0.399,(6) product quality has a positive and significant effect on customer satisfaction through wit's purchasing decisions h the significance of 0,000 and a regression coefficient of 0.158(7)benefit has a positive and significant effect on customer satisfaction through purchasing decisions with significance of 0,000 and a regression coefficient of 0.210.